(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The essay traces the main stages of constitutional jurisprudence on artificial insemination, taking the science/law dialectic as a perspective point of view. The essay dwells on the vulnus that the rhetorical use of the scientific argument causes to the overall coherence of the legal system and in this perspective analyses the most recent decisions of the constitutional judge on the status of children born of procreative techniques still prohibited in Italy.